IMPLEMENTASI PEMBELAJARAN BERBASIS BUDAYA TERHADAP KARAKTER PESERTA DIDIK SEKOLAH DASAR - Juliani, Ai; Karmilasari, Karmilasari; Agustiani, Tini; Mulyanah, Dede; Windiyani, Tustiyana (Jurnal Pendidikan Dasar, 2024)
Abstract: The novelty of this article is to find a new way of learning in primary schools that uses culture-based learning in relation to the character of students in primary schools. The aim of this study is to describe the results of research related to the implementation of culture-based learning on the character of primary school students. The findings in these articles are then used as a basis for formulating new paths when discussing culture-based learning on student character. The method used in this study is a literature search of good articles in Indonesian in 2016-2023 sourced from the Google Scholar and Garuda search sites with the keywords “implementation of culture-based learning on the character of primary school students. The data- analysis procedure was carried out based on a qualitative approach. The research results show that culture-based learning on the character of primary school students can be implemented in indoor, co-curricular and extracurricular activities. Cultural elements that can be applied in learning, such as traditional games, dances and folklore. In addition, the character values expressed in culture-based learning include cooperation, self-confidence, honesty, responsibility, tolerance, mutual respect, discipline and love for the motherland.